The key : how corporations succeed by solving the world's toughest problems - Gratton, Lynda (McGraw-Hill Education, 2014)
Lynda Gratton maps out how bringing resilience to a fragile world starts with what happens inside a corporation--when intelligence and wisdom are amplified, emotional vitality enhanced, and social connections harnessed. She explains how corporations can leverage this inner resilience to help solve global problems and how a corporation's unique innovative, scaling and mobilizing, and alliance building capabilities are some of the tools for combating global ills. Both realistic and optimistic, this is a guide that provides the rationale, strategies, and tools you need to not only spearhead resilience for your own company but also how to use this resilience to contribute to the betterment of the world. She provides insights from more than 20 companies from across the world including Vodafone, Unilever, Tata Consulting Services, and Natura to illustrate the very real benefits of aligning organizational interests with those of the world. --